Neospora caninum serostatus is affected by age and species variables in cohabiting water buffaloes and beef cattle - Moore, Dadin Prando (2014)
The aim of this study was to investigate how Neospora caninum serostatus may be affected by variables such as host species (water buffaloes or cattle) and age in animals cohabiting in the same ranch. A convenience cross-sectional study was performed on four ranches in the Northeast of Argentina, where water buffalo are cohabitating with beef cattle. Blood samples were collected from 1350 female water buffaloes (Bubalus bubalis) and 880 female beef cattle (Bos taurus and Bos indicus crossbreeds) from four ranches. Calving and weaning percentages at herd level for each ranch were also recorded. N. caninum antibody levels were measured by an indirect fluorescent antibody test (IFAT) (reciprocal antibody titers ≥100). Serological results were classified into 2 categories (0: negative; 1: positive). A logistic regression model was used to describe the relationship between N. caninum serostatus and specie (water buffalo or cattle), age or ranch and their interactions. Likelihood ratio tests were used to assess the significance of the model and their terms. Odds ratios were estimated and 95% profile likelihood (LR) and Wald confidence intervals (CI) obtained. Overall, specific antibody titers were found in 43.3% (584/1350) of water buffaloes and 28.6% (252/880) of cattle. Seropositive water buffaloes and cattle were observed on all ranches. Age was statistically significant (p = 0.01) with an overall estimate of logit (log odds) of age of 0.03 for both species. This indicates that for every one year increase in age, the expected change in log odds of being seropositive increased by 0.03. On three of four ranches a water buffalo was 4.48, 1.54 and 2.25 times more likely to be seropositive than cattle for animals of the same age. The N. caninum serostatus was affected by age in the first place, but also by species on at least three of the four ranches. Calving and weaning percentages were higher in water buffaloes than in beef cattle (p < 0.05). Even though the low pathogenicity that N. caninum seems to have in water buffaloes, this study reinforces the importance of this specie as maintenance of the disease.